Allelic and Genotypic Analysis of LncRNA ANRIL rs4977574 A/G Mutations in Oral Squamous Cell Carcinoma Patients: Insights into Tumor Characteristics and Genotypic Correlations - Mohammad Amin Amiri; Delara Amiri; Mohammad Javad Mokhtari; Fatemeh Lavaee; Mohammad Javad Fattahi; Abbas Ghaderi; Bijan Khademi (International Journal of Dentistry)
Aim. Long noncoding RNAs (lncRNA) ANRIL and its genetic polymorphisms are shown to be associated with the risk of several cancers. However, the single nucleotide polymorphisms (SNPs) of lncRNA ANRIL are not thoroughly assessed in oral squamous cell carcinoma (OSCC) which is the most prevalent cancer in the head and neck area. Thus, this study aimed to assess the association of SNP of lncRNA ANRIL rs4977574 in patients with OSCC. Methods and Materials. 106 blood samples from the patients with OSCC were obtained with a gender- and age-matched control group to evaluate the SNP of rs4977574 of lncRNA ANRIL. The DNA was extracted using the salt-out technique and DNA genotyping was undertaken using specific primer pairs in the tetra-primer ARMS-PCR technique. Eventually, the frequency of wild-type (A) and the mutated allele (G), as well as the genotypes were estimated between the groups of patients with OSCC and healthy individuals. Results. The results of our study indicated no statistically significant difference in the frequency of rs4977574 A/G of lncRNA ANRIL among the patients with OSCC and healthy individuals (p>0.05). Likewise, no significant difference was found in the genotypes’ frequencies (p>0.05). Nevertheless, the marked association of GG with smaller tumor size and the high level of differentiation of OSCC cells in the presence of AA or AG genotypes were interesting outcomes of this study (p<0.05). Similarly, all the genotypes AA, AG, and GG were correlated with the site of the occurrence of OSCC. Furthermore, the association of the genotypes with the lymph node metastasis and the tumors stage was not found to be significant (p>0.05). Conclusions. The results of our study indicate that rs4977574 A/G and its genotypes do not have any direct correlation with the presence of OSCC; however, its association with the smaller tumor size and the level of the cancer cells differentiation could imply its possible indirect role.